PERAN UMAT ISLAM DALAM MEWUJUDKAN MASYARAKAT MADANI DI INDONESIA - Ngudi Astuti (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2012)
The concept of civil society refers to the ideal model of community life in Medina the Prophet Muhammad, which is based on a constitution that called the Charter of Medina. Madani Society is islamization of civil society. Strategies to build madani society in Indonesia can be done with the national integration and political, democratic political system reform, education and political awareness. The role of Muslims in the realization of madani society are as agents of change against the emergence and growth of the intellectuals among the middle class to create the order of social life in a democratic political-economic system is fair.